2018
DOI: 10.1016/s1130-8621(18)30176-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and association between triglyceride level and lifestyle factors among Malay obese class I and II adults

Abstract: The findings of this study highlighted elevated triglyceride level in obese adults might be influenced by unhealthy lifestyle behaviors. We suggest that lifestyle modification intervention is appropriate to prevent cardiovascular disease among Malay obese class I and II adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…One of strong contributory factor to obesity is unhealthy lifestyle practices by Malaysian women. 16 This study finding support with previous finding where unemployed women spent more time in sitting compared to those who are working.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One of strong contributory factor to obesity is unhealthy lifestyle practices by Malaysian women. 16 This study finding support with previous finding where unemployed women spent more time in sitting compared to those who are working.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies found that prolonged sitting time at work and also at leisure time and even during transportation were affects their health concern. 17 Their study also shows that sedentary behavior is associated with cardiovascular disease that leads to mortality. Study conducted by Choi et al, 8 found that prolonged total sitting time per day at least 16 h will increase the risk of cardiovascular disease compared to less than 4 h sitting.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The finding was supported by studies conducted in Malaysia and India. 5,11 In this study the triglyceride level was equal in both the sexes. The study also did not show the significant association between sex and BMI.…”
Section: Discussionmentioning
confidence: 55%
“…3,4 Obesity encourages TG accumulation at the cellular level by slowing the rate of lipid turnover. 5 In addition, excessive adipocytes in obese adults enhanced the release of free fatty acids (FFAs). 6 According to Nepal Demographic and Health Survey 2016, the prevalence of overweight or obese among women was 22% and in men the prevalence was 17%.…”
Section: Introductionmentioning
confidence: 99%